Natural course of Fabry disease: changing pattern of causes of death in FOS – Fabry Outcome Survey. Issue 8 (26th May 2009) - Mehta, A; Clarke, J T R; Giugliani, R; Elliott, P; Linhart, A; Beck, M; Sunder-Plassmann, G; ,
Abstract : Background: Fabry disease is a rare X-linked lysosomal storage disorder characterised by severe multisystemic involvement that leads to major organ failure and premature death in affected men and women. Over the past 7 years, the Fabry Outcome Survey (FOS) has collected data on the natural history of Fabry disease, and the long-term efficacy and safety of enzyme-replacement therapy. This paper provides an update on the first analysis of FOS data. Design: Baseline data on clinical manifestations and causes of death in a cohort of 1453 patients (699 male, 754 female) from 19 countries worldwide were analysed. Causes of death of affected relatives were analysed separately. Results: The most frequently reported signs and symptoms of Fabry disease were neurological. Cardiac, ocular, gastrointestinal, dermatological, auditory and renal manifestations were also common. The principal causes of death among 181 affected relatives of patients in FOS (most of whom had died before 2001) were renal failure in males (42%) and cerebrovascular disease in females (25%). In contrast, of the 42 patients enrolled in FOS whose deaths were reported between 2001 and 2007, cardiac disease was the main cause of death in both male (34%) and female (57%) patients. Conclusion: These data suggest that the importance of renal disease as a cause of death in patients with Fabry disease is decreasing while the importance of cardiac disease is increasing. This pattern probably reflects improvements in the management of renal disease in patients with Fabry disease.